Mga Kalamidad at ang Rebelyong Dios-Dios sa Samar noong Dantaon 19 - Abejo, Raymund Arthur G. (Philippine Social Sciences Review; Recent Studies in Philippine History, Eds., Laura Samson and Ricardo Jose, 2010)
Samar, one of the poorest islands in the Philippines since the colonial period to the present, was at the margin of the major transformations in the archipelago during the nineteenth century. Encouraged by inter-island shipping and the opening of Cebu and Iloilo ports to international trade, cash crop productions increased and population grew in Samar. Abaca, coconut oil, and dried fish were its major products. During this century the Philippines also experienced several calamities and epidemics. The impact of calamities such as typhoons, locust plagues and cholera epidemics on the lives of the people of Samar during the nineteenth century is examined in the paper. It describes the destruction and death caused by typhoons in 1842, 1843, 1879, 1882 and 1893; locust plagues in 1855-1858 and 1885-1887, and cholera epidemics in 1821-1823, 1846-1847, 1850 and 1882-1883. This paper explores the relationship between these calamities and the outbreak of Dios-Dios rebellion throughout the island. Drawing from archival records and travel accounts of that period, the emergence of Dios-Dios as a social movement is considered as an outlet of resistance to Spanish colonial rule and a reaction to the sufferings brought by the calamities.